Implementing The Process Writing Approach To Improve The Ability Of The Students In Writing Procedure Text - Zainuddin; Harta Winata, Vivin (LP3M UNZAH GENGGONG, 2020)
This study is designed to improve the ability of the students in writing by using Process Writing Approach. Consequently, the research problem formulated in this research is “How can Process, Writing Approach be implemented to improve the ability of the tenth grade students of SMAN 2 Probolinggo in writing procedure text”. To answer the problem, a classroom action research design was used on April 22, 2019 until May 15, 2019.This study belongs to Classroom Action research (CAR) chose it because writing procedure text conducting in that semester. The preliminary test indicates that only 4 students scored above the suggested mastery learning of 78. The target was achieved in second cycles. Based on the finding above, it is recommended that procedure writing approach can be implemented to improve of the student’s ability in writing procedure text. Beside the result of the study showed that the students were enthusiastic, motivated and actively involved in teaching and learning process. Key words: Students writing ability, procedure text, process writing approach.